PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PENGENALAN SATWA LANGKA YANG DILINDUNGI DI INDONESIA BERBASIS AUGMENTED REALITY - Rifda Choirunnisa; Apri Utami Parta Santi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the need for digital learning media that is attractive, easy to use, and able to facilitate students' understanding of the material in learning Natural and Social Sciences (IPAS). The purpose of the research is to develop interactive learning media based on Augmented Reality on the material "Introduction to endangered species protected in Indonesia" in Elementary Schools. The method used in this research is Research and Development (R&D) with the DDD-E development model (Decide, Design, Develop, Evaluate). The data collection technique used in this research is a questionnaire instrument. This learning media has been validated by material experts, language experts, and media experts, and tested on teachers and sixth grade students at SDN CILANDAK BARAT 07. The results of the study show that the learning media is in the very valid and very practical category, evidenced by the validation questionnaire by media experts obtaining a score of 96% very valid, material experts obtaining a score of 92% very valid, and language experts obtaining 95% very valid, as well as the results of the questionnaire by teachers obtaining 96%, student response questionnaires in small groups 83% and large groups obtaining 90% with a very practical category. Thus, this Augmented Reality-based learning media is very valid and very practical to be used as an alternative in the science learning process, especially in the introduction of endangered species protected in Indonesia to increase students' interest, motivation, and understanding of the material presented.